2017
DOI: 10.3233/aac-170015
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and personality traits in argumentation: An empirical evaluation1

Abstract: Abstract. Argumentation is a mechanism to support different forms of reasoning such as decision making and persuasion and always cast under the light of critical thinking. In the latest years, several computational approaches to argumentation have been proposed to detect conflicting information, take the best decision with respect to the available knowledge, and update our own beliefs when new information arrives. The common point of all these approaches is that they assume a purely rational behavior of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…This is not surprising, however, concerns are often ignored when judging the effectiveness of arguments or choosing a strategy. There are some studies that make use of different personality traits of the user attributes in order to evaluate what sort of argument might be more effective for this particular person (for examples see [13,9,23,19]). However, computational argumentation largely focuses on sentimental [7], rhetorical [11] and structural [4] attributes of the argument, rather than attributes about the user.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, however, concerns are often ignored when judging the effectiveness of arguments or choosing a strategy. There are some studies that make use of different personality traits of the user attributes in order to evaluate what sort of argument might be more effective for this particular person (for examples see [13,9,23,19]). However, computational argumentation largely focuses on sentimental [7], rhetorical [11] and structural [4] attributes of the argument, rather than attributes about the user.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that the emotions reflected from the participants' arguments are strongly connected to the argumentation processes. If the arguments are in opposition, the emotions reflected from them tend to be negative related; similarly, the emotion tends to be positive if arguments support to each other (Benlamine et al, 2015; Villata et al, 2017). As an engine of argumentation, emotions play an active role in decision taking as modifiers of theory‐of‐mind models, goals and strategies (Martinovski & Mao, 2009).…”
Section: Related Workmentioning
confidence: 99%
“…This was only observed in the scenario in which participants were asked to evaluate an anti-conservation claim, so it is plausible that simply hearing an anticonservation claim elicited negative emotions. Indeed, Villata et al (2017) found that conflicting opinions during debate elicit negative emotions. Further, these negative emotions seemed to have compelled participants to evaluate the claim with more skepticism.…”
Section: Emotion and Scientific Argumentationmentioning
confidence: 99%